Editorial - Braude, Stephen (Journal of Scientific Exploration, 2012)
In addition to the usual array of interesting papers and reviews, this issue of the JSE features a debate that I consider especially noteworthy. The topic of the debate is hypnosis and the participants in the dialogue are all recognized authorities on the subject. However, the backgrounds and perspectives of the participants are also quite different, and so the discussion of the issues is commendably broad and wide-ranging. I’ve often wondered whether JSE readers noticed and were puzzled by the fact that hypnosis has received little (if any) attention in the pages of this Journal. It has certainly puzzled me. Granted, unlike some of the phenomena (or alleged phenomena) discussed in the JSE, the existence of hypnosis is not generally disputed. However, the process and nature of hypnosis, and the implications of hypnotic phenomena for our understanding of the mind, remain acknowledged mysteries. To be sure, a small number of researchers cling obdurately to the belief (associated perhaps most often with Nicholas Spanos) that hypnosis is nothing but social compliance or role-playing designed to please the hypnotist.1 But the transparent absurdity of that position becomes clear as soon as one considers some of the more dramatic hypnotic phenomena—for example, failing to register pain during major surgery (e.g., limb amputation, the removal of 100-lb scrotal tumors [yes, that’s right], and the removal of toenails by the roots), and also the prevention of well-known involuntary responses to other noxious stimuli, such as ammonia placed under the nose and needles inserted in the mucous membranes of the eyes. Clearly, the subjects in these cases aren’t simply complying with the wishes of the surgeon by (say) feigning a lack of pain. These are paradigm cases of genuine and profound—and poorly understood—altered states, and they’re quite different from the non-reactions to relatively mild pain (e.g., hands in ice water) considered by Spanos. .....